Small architecture now! : Kleine Bauten = Petite architecture - Jodidio, Philip (Taschen, 2014)
Over the years, talented architects have occasionally indulged themselves with the challenge of designing small but perfectly formed buildings. Today, with reduced budgets, many architects have turned in a more focused way to creating works that may be in diminutive in their dimensions, but which are definitely big when it comes to trendsetting ideas. Whether in Japanese cities, where large sites are hard to come by, or at the frontier between art and architecture, small buildings present many advantages, and push their designers to do more with less. A dollhouse for Calvin Klein in New York, a playhouse for children in Trondheim, pop-up stores for fashion stars, vacation cabins, or housing for victims of natural disasters are all part of the new rush to develop the great small architecture of the moment. The 2013 Pritzker Prize winner Toyo Ito is here, but so are emergent architects from Portugal, Chile, England, and New Zealand. Alvaro Siza and Kazuyo Sejima (SANAA) display their eye for tiny detail alongside artists Doug Aitken and Olafur Eliasson.